Pentafluorophenyl Ester‐based Polymersomes as Nanosized Drug‐Delivery Vehicles. Issue 1 (19th October 2015) - Scherer, Martin; Fischer, Karl; Depoix, Frank; Fritz, Thomas; Thiermann, Raphael; Mohr, Kristin; Zentel, Rudolf
Abstract : In this work, activated ester chemistry is employed to synthesize biocompatible and readily functionalizable polymersomes. Via aminolysis of pentafluorophenyl methacrylate‐based precursor polymers, an N ‐(2‐hydroxypropyl) methacrylamide (HPMA)‐analog hydrophilic block is obtained. The precursor polymers can be versatile functionalized by simple addition of suitable primary amines during aminolysis as demonstrated using a fluorescent dye. Vesicle formation is proven by cryoTEM and light scattering. High encapsulation efficiencies for hydrophilic cargo like siRNA are achieved using dual centrifugation and safe encapsulation is demonstrated by gel electrophoresis. In vitro studies reveal low cytotoxicity and no protein adsorption‐induced aggregation in human blood serum occurs, making the vesicles interesting candidates as nanosized drug carriers. Abstract : The formation of polymersomes from HPMA‐related amphiphilic blockcopolymers is presented. These polymers are prepared via activated ester chemistry, which allows efficient and facile modification. The vesicles formed from them exhibit high encapsulation efficiencies for hydrophilic cargo via dual centrifugation. Furthermore, they prove to be biocompatible, which makes them promising candidates as nanosized drug carriers.